C-Type Lectin-Like Receptors of the Dectin-1 Cluster: Ligands and Signaling Pathways - Plato, Anthony (Informa Healthcare, 2013)
Innate immunity is constructed around genetically encoded receptors that survey the intracellular and extracellular environments for signs of invading microorganisms. These receptors recognise the invader and through complex intracellular networks of molecular signaling, they destroy the threat whilst instructing effective adaptive immune responses. Many of these receptors, like the Toll-like receptors in particular, are well-known for their ability to mediate downstream responses upon recognition of exogenous or endogenous ligands; however, the emerging family known as the C-type lectin-like receptors contains many members that have a huge impact on immune and homeostatic regulation. Of particular interest here are the C-type lectin-like receptors that make up the Dectin-1 cluster and their intracellular signaling motifs that mediate their functions. In this review, we aim to draw together current knowledge of ligands, motifs and signaling pathways, present downstream of Dectin-1 cluster receptors, and discuss how these dictate their role within biological systems.